Ex officio control of international jurisdiction, determination of the applicable law to the matrimonial property regime and realization of the scope and burden of proof of foreign law. For the purpose of judgement no. 1402/2021 of the Málaga Provincial C - Álvarez Agoués, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The judgment of the Provincial Court of Malaga (Sixth Section) of October 18, 2021 partially upholds the appeal filed and partially revokes the ruling issued on July 15, 2019 by the Court of Violence against Women No. 1 of Malaga. The origin of the litigation lies, in the framework of a marital breakdown or crisis with an international component, in the inventory linked to the procedures for the liquidation of the community property formed by the spouses. At the same time, the necessary determination of the applicable law to the matrimonial property regime (Russian Law) is raised as well as the question linked to the proof of such foreign legal order.-me, pleading and evidence in foreign law.
Keywords: Conflict rule identification; selection applicable law to the matrimonial property regime; pleading and evidence in foreign law